Living with “slow upheavals”: unsettling a resilience-based approach in Ittoqqortoormiit (Kalaallit Nunaat) - Sandré, Tanguy; Vanderlinden, Jean-Paul; Wardekker, Arjan; Gherardi, Jeanne (Frontiers in Climate, 2025)
IntroductionThis article explores how narratives of changes reflect concerns about latent threats to the material and immaterial dimensions of individual and collective lives. Using decolonial approaches and critical ethnography practices in Ittoqqortoormiit (East Kalaallit Nunaat), we empirically challenge resilience frameworks by expanding the body of research on slow violence—unsensational, gradual harm that exacerbates the vulnerabilities of ecosystems, non-human entities, and disempowered individuals and groups—in the context of transdisciplinary and community-based climate change research.MethodsWe conducted repeated stays in the community from 2019 to 2023 and practiced deep-hanging and critical ethnography. Our results are supported by the analysis of 33 open-ended interviews.ResultsThe research participants provided valuable insights, characterizing changes as slow upheavals, which we define as events that are not sudden or whose impacts manifest gradually and whose severity and salience are subject to deliberation. Local experiences do not align with narratives of rapid change and also contest modern ontologies that depict the world as stable and controllable. Instead, they express alternative onto-epistemologies of living in or “becoming-with” evolving worlds.DiscussionThrough a dialog with critiques of colonial and neoliberal interpretations or approaches to resilience, we demonstrate the centrality of place-attachment in supporting agency and hope amid experiences of marginalization. We point out the need to move toward agency-based resilience frameworks that take account of lived experiences. We encourage listening to diversified discourses on the climate and ecological crisis, which is inextricably intertwined with the multidimensional upheavals experienced by diverse communities in the Arctic and beyond.